Impacts of prolonged sitting with mild hypercapnia on vascular and autonomic function in healthy recreationally active adults - Headid, Ronald J.; Pekas, Elizabeth J.; Wooden, TeSean K.; Son, Won-Mok; Layec, Gwenael; Shin, John; Park, Song-Young (American journal of physiology. Heart and circulatory physiology, 2020)
The results of this study reveal that prolonged sitting attenuates endothelial function and microvascular function. Additionally, prolonged sitting with mild hypercapnia, which is similar to everyday environments, further exacerbates peripheral endothelial function and microvascular function. Prolonged sitting, which is known to impair peripheral vascular function, often occurs in spaces (e.g., offices) with mild hypercapnic atmospheres. However, the effects of prolonged sitting in hypercapnic conditions on vascular function are unknown. Therefore, the purpose of this study was to investigate the effects of prolonged sitting in mild hypercapnic conditions on vascular and autonomic function in humans. Twelve healthy young adults participated in two experimental visits that consisted of sitting for 2.5 h in a control condition [normal atmospheric conditions sitting (PSIT)] or a mild hypercapnic condition (HCAP; CO 2 = 1,500 ppm). During each visit, heart rate variability (HRV), blood pressure (BP), pulse wave velocity (PWV), augmentation index (AIx), brachial and popliteal artery flow-mediated dilation (FMD), and near-infrared spectroscopy (NIRS) were assessed before and after prolonged sitting. Sitting significantly decreased AIx in both groups ( P < 0.05). Brachial and popliteal FMD were reduced with sitting ( P < 0.05), and the reduction in popliteal FMD was amplified by HCAP ( P < 0.05). Baseline microvascular oxygenation was decreased following sitting in both groups ( P < 0.05). However, microvascular reoxygenation upon cuff release was slower only in HCAP ( P < 0.05). HRV, HR, BP, and PWV did not significantly change with sitting in either group ( P > 0.05). We conclude that prolonged sitting attenuated both brachial and popliteal endothelial function and was associated with perturbed microcirculation. Additionally, mild hypercapnic conditions further impaired peripheral endothelial and microvascular function. Together, these findings suggest that prolonged sitting is accompanied by a host of deleterious effects on the vasculature, which are exacerbated by mild hypercapnia. NEW & NOTEWORTHY The results of this study reveal that prolonged sitting attenuates endothelial function and microvascular function. Additionally, prolonged sitting with mild hypercapnia, which is similar to everyday environments, further exacerbates peripheral endothelial function and microvascular function. Listen to this article's corresponding podcast at https://ajpheart.podbean.com/e/vascular-response-to-prolonged-sitting-in-hypercapnia/ .